2015
DOI: 10.3390/ncrna1030170
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus EBER Transcripts Affect miRNA-Mediated Regulation of Specific Targets and Are Processed to Small RNA Species

Abstract: The oncogenic Epstein-Barr virus (EBV) expresses 44 mature microRNAs and two non-coding EBER RNAs of 167 (EBER1) and 172 (EBER2) nt length. MiRNA profiling of NK/T cell lines and primary cells and Northern blotting of EBV-infected cell lines and primary tumors revealed processing of EBER1 to short 5′-derived RNAs of approximately 23, 52 and 70 nt (EBER123, EBER152, and EBER170) and of EBER2 to 3′ fragments. The biogenesis of these species is independent of Dicer, and EBER123 does not act like a miRNA to target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Significantly, EBER1/2 cooperated with BART16 in the specific down modulation of the S1PR1 3 0 UTR (P = 0.002). In conjunction with the previous report showing that BART16 had no effect on TOMM22 [28], this again illustrates that the effect of the EBERs are specific for a given miRNA vis-a-vis its mRNA target.…”
Section: Identification Of New Targets For Viral and Deregulated Hostsupporting
confidence: 84%
See 4 more Smart Citations
“…Significantly, EBER1/2 cooperated with BART16 in the specific down modulation of the S1PR1 3 0 UTR (P = 0.002). In conjunction with the previous report showing that BART16 had no effect on TOMM22 [28], this again illustrates that the effect of the EBERs are specific for a given miRNA vis-a-vis its mRNA target.…”
Section: Identification Of New Targets For Viral and Deregulated Hostsupporting
confidence: 84%
“…B). We have recently shown that coexpression of the EBV‐encoded EBER RNAs co‐represses certain targets such as down modulation of IL‐1α by miR‐142‐3p but had no effect on the regulation of TOMM22 by ebv‐miR‐BART16 . Expression of EBER1/2 also down modulated the empty vector and coexpression with BART16 increased this.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations